2015
DOI: 10.1007/s12094-015-1291-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung metastases in oligometastatic patients: outcome with stereotactic body radiation therapy (SBRT)

Abstract: SBRT is effective and safe. The main failure pattern is distant progression. The selection of patients with a high probability of remaining oligometastatic is crucial for the efficiency of SBRT, both clinically and in terms of resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 19 publications
2
21
1
Order By: Relevance
“…Radiotherapy dose escalation improved local control. The 5‐year TMC of 69% in patients who received a minimum dose of 36 Gy in 3 fractions fell within the 65% to 95% range of local control rates published in similar SBRT experiences, most of which had shorter follow‐up . Other institutions have observed that escalation to biologically effective doses >100 Gy was needed to achieve approximately ≥90% local control .…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Radiotherapy dose escalation improved local control. The 5‐year TMC of 69% in patients who received a minimum dose of 36 Gy in 3 fractions fell within the 65% to 95% range of local control rates published in similar SBRT experiences, most of which had shorter follow‐up . Other institutions have observed that escalation to biologically effective doses >100 Gy was needed to achieve approximately ≥90% local control .…”
Section: Discussionmentioning
confidence: 63%
“…The 5-year TMC of 69% in patients who received a minimum dose of 36 Gy in 3 fractions fell within the 65% to 95% range of local control rates published in similar SBRT experiences, most of which had shorter followup. [6][7][8][9][10][11][12][13] Other institutions have observed that escalation to biologically effective doses >100 Gy was needed to achieve approximately 90% local control. 8,13,24 Like other reports, dose escalation in our cohort failed to improve OS, likely because of high rates of failure outside of treated lesions and eventual polymetastatic progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the optimal prescription dose still needs further investigation. Former studies have proven that biologically effective doses (BED) of over 105 Gy are required for increased local control rates [7,12]. When delivering an increased fraction dose to the tumor, the risk of normal tissue toxicity can increase.…”
Section: Introductionmentioning
confidence: 99%